Impacts of Amine Functionalized Iron Oxide Nanoparticles on HepG2 Cell Line - Ebrahiminezhad, Alireza; Rasoul-Amini, Sara; Kouhpayeh, Amin; Davaran, Soodabeh; Barar, Jaleh; Ghasemi, Younes (Current Nanoscience, 2015)
Iron oxide nanoparticles (IONs) are being used in medicine for magnetic resonance imaging, drug delivery and hyperthermia. There are contradictory data about cytotoxic effects of IONs on various cell lines. In this study a couple of IONs with two biocompatible coatings, L-lysine and 3-aminopropyltriethoxysilane, were synthesized by coprecipitation method in aqueous matrix and characterized. The MTT assay was used to evaluate the effects of the synthesised IONs on HepG2 cells. Cell culture illustrated that the growth of HepG2 cells can be promoted by IONs and nanoparticles with biocompatible coating have more biological benefit impacts than naked particles. By increase in concentration, cytotoxic effects will appear and reduce the growth promotion effects. Cytotoxic effects are in relation with agglomeration degree of nanoparticles, agglomeration can reduce cytotoxicity of IONs at high concentrations.
Keywords: Cytotoxicity